Clinical manifestations and outcomes of patients with intravascular large B-cell lymphoma with neurological involvement: highlighting longitudinally extensive myelopathy as a distinct feature - Jiraporn Jitprapaikulsan; Ekdanai Uawithya; Palakorn Lertsakworakul; Weerapat Owatthanapanich (BMJ Neurology Open)
Objective This study aimed to elucidate the clinical manifestations, laboratory findings and outcomes of patients with intravascular large B cell lymphoma (IVLBCL) with neurological involvement and to differentiate IVLBCL with and without neurological involvement.Methods A cohort study was conducted at Siriraj Hospital, Mahidol University, Thailand, between January 2005 and September 2024. Clinical data, laboratory values and central nervous system imaging results were analysed. Categorical variables were compared using the χ² or Fisher’s exact test, while continuous variables were analysed with the Mann-Whitney U test, as appropriate.Results Of the 30 patients with IVLBCL, 10 had neurological involvement and 20 without neurological symptoms, including myelopathy (5 patients, 50%); cognitive impairment (3 patients, 30%); seizures (2 patients, 20%); optic neuropathy, hemiparesis, homonymous hemianopia, vertigo and global aphasia (each affecting 1 patient, 10%). 60% of IVLBCL with neurological involvement had systemic symptoms, including prolonged fever, anaemia, anorexia and weight loss. MRI showed hyperintense lesions in the supratentorial, infratentorial and spinal cord with the prominent findings being longitudinally extensive cord lesions (four patients, 40.0%). The median survival time of the IVLBCL with neurological involvement was 4.1 months (95% CI: 0.0 to 17.1 months), with a 1-year survival rate of 37.5% and a 2-year survival rate of 25.0%.Interpretation This study highlights the distinct clinical, laboratory features and imaging of IVLBCL with neurological involvement and compares it to IVLBCL without neurological involvement. Early recognition of these findings is crucial for accurate diagnosis and improved patient outcomes despite the aggressive nature of IVLBCL.